Towards the Development of the Future Internet Based Enterprise in the Context of Cyber-Physical Systems - Sacala, Ioan Stefan; Moisescu, Mihnea Alexandru; Repta, Dragos (2013 19th International Conference on Control Systems and Computer Science, 2013)
The constantly increasing dynamics of the world economy and the shift of business values in accordance with the new values of the current society has lead to the development of new Internet oriented Enterprise Systems. This paper is concerned with the transformation of such systems in regard to the new paradigms of Future Internet and Cyber - Physical Systems. A Distributed Semantic Middleware is proposed as an Enabler for the development of Cyber Enterprise Systems.